2020
DOI: 10.5194/acp-20-1777-2020
|View full text |Cite
|
Sign up to set email alerts
|

The global impact of bacterial processes on carbon mass

Abstract: Abstract. Many recent studies have identified biological material as a major fraction of ambient aerosol loading. A small fraction of these bioaerosols consist of bacteria that have attracted a lot of attention due to their role in cloud formation and adverse health effects. Current atmospheric models consider bacteria as inert quantities and neglect cell growth and multiplication. We provide here a framework to estimate the production of secondary biological aerosol (SBA) mass in clouds by microbial cell grow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 120 publications
2
26
0
Order By: Relevance
“…While phenol is not a major contributor to the WSOC content in cloud water (5-95 nM ) (Jaber et al, 2020) as compared to 10µm (Ervens et al, 2003b) (Löflund et al, 2002) (Sun et al, 2016) for formic and acetic acids respectively, its degradation processes in the atmosphere might be of interest due to its toxic properties. Overall, our results are in agreement with previous findings that neither chemical processes nor biodegradation are major WSOC 530 losses as compared to deposition (Ervens and Amato, 2020) (Fankhauser et al, 2019). However, in order to comprehensively describe the loss processes and time scales of organic degradation and residence time scales in the atmosphere, both chemical and biological processes should be considered.…”
Section: For Which Organics Is Biodegradation An Efficient Sink In Thsupporting
confidence: 92%
See 1 more Smart Citation
“…While phenol is not a major contributor to the WSOC content in cloud water (5-95 nM ) (Jaber et al, 2020) as compared to 10µm (Ervens et al, 2003b) (Löflund et al, 2002) (Sun et al, 2016) for formic and acetic acids respectively, its degradation processes in the atmosphere might be of interest due to its toxic properties. Overall, our results are in agreement with previous findings that neither chemical processes nor biodegradation are major WSOC 530 losses as compared to deposition (Ervens and Amato, 2020) (Fankhauser et al, 2019). However, in order to comprehensively describe the loss processes and time scales of organic degradation and residence time scales in the atmosphere, both chemical and biological processes should be considered.…”
Section: For Which Organics Is Biodegradation An Efficient Sink In Thsupporting
confidence: 92%
“…Marker compounds such as adenosine 5'-triphosphate (ATP) (Amato et al, 2007c) , rRNA 50 (Krumins et al, 2014) or mRNA (Amato et al, 2019) have been used to demonstrate metabolic activity in the atmosphere. Metabolic activity and cell generation of bacteria is likely restricted to the time cells spent in clouds due to the abundance of liquid water (Haddrell and Thomas, 2017) (Ervens and Amato, 2020); bacteria have been found to be dormant at lower relative humidity than in clouds (Kaprelyants and Kell, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…57,58 However, once entered the atmosphere, OM undergoes complex changes; first, abiotically due to chemical reactions, e.g., with OH and NO 3 radicals, and also biologically by microbial degradation. 59,60 Latest studies revealed that airborne bacteria can survive in the atmosphere even in the harsh polar environments and are, similar to bacteria in seawater, metabolically active in the aqueous phase of clouds, as well as on the surface or in the bulk of aerosol particles. 59−63 However, airborne bacteria do not only degrade available OM, but they also release new organics, as it was shown for EPS in cloud water.…”
Section: Introductionmentioning
confidence: 99%
“…Current atmospheric multiphase chemistry models include chemical mechanisms of different complexity with up to thousands of chemical reactions describing the transformation of inorganic and organic compounds, e.g., (Ervens et al, 2003a;Mouchel-Vallon et al, 2017;Tilgner et al, 2013;Woo and McNeill, 2015). However, they do not include the biodegradation of organics by bacteria despite the available data sets discussed above.…”
Section: A Khaled Et Al: Biodegradation By Bacteria In Cloudsmentioning
confidence: 99%